PELAYANAN PUBLIK PADA PENERAPAN INOVASI ONE DAY SERVICE DI KABUPATEN TABANAN DESA JATILUWIH - Dwi Widari, Ni Made; Dony Indrayana, I Putu; Gede Widiana, I Nyoman (Universitas Panji Sakti, 2025)
Bali Province, Tabanan Regency is one of the regions in Indonesia that provides public services as stated in Law Number 25 of 2009 concerning public services, which is a series of activities to fulfill the service needs of the community for goods, services and/or administrative services provided by the organizer. public service. Public Management is a process of planning, directing, organizing and supervising businesses, agencies of member organizations with various other organizational resources in order to achieve goals. Through breakthrough new innovations through One Day Service which provides birth certificate services. The aim of this research is to describe Onne Day Service innovation in Tabanan Regency, Jatiluwih Village using the theory of Parasuraman, Zeitaml, and Berry on formative factors expected service (expected service) provides options or SOPs for providing services to the public in accordance with bureaucratic criteria and arrangements that can help or make things easier for the public (society). The role of regional leaders with local wisdom can also help to educate and provide a mechanism for each banjar to carry out orderly administration as a form of population data collection and a means of identifying children from birth so that they are recognized in the country where they live.